Aesthetic experiences of patients with advanced cancer in end-of-life care in China: A phenomenological study - Li, Xia; Kongsuwan, Waraporn; Barry, Charlotte D. (Belitung Raya Publisher - Belitung Raya Foundation, 2025)
Background: For most patients with advanced cancer, an important prerequisite for quality of end-of-life care is understanding their preferences. Nurses reported the challenges in the care process, such as poor communication patterns of sensitive topics. Aesthetic experience values meaningful moments and is sensitive to the impact of different environments and situations. Aesthetic expression enables individuals to transform intuitive cognition into artistic behavior, ultimately expressing real needs through aesthetic cognition, enhanced sensibility, and reflection, thereby promoting improved care quality. However, there is still a lack of studies exploring aesthetic experiences in end-of-life care from the perspective of patients with advanced cancer. Objective: To explore the aesthetic experiences in end-of-life care as perceived by patients with advanced cancer during hospitalization. Methods: This study applied a hermeneutic phenomenological approach and was conducted in an oncology unit of a hospital in China. This hospital was the hospital promulgated by the local health department as a pilot hospice care program. The hospital mainly admitted patients with advanced cancer who have given up radiotherapy and chemotherapy after being treated in a higher-level hospital. Data collection spanned from August to December 2023. Ten participants were invited to engage in reflective experiences using the individual face-to-face interviews followed by the creative drawings. The data were analyzed and interpreted following van Manen’s approach. Results: The findings revealed four themes: 1) Dynamic understanding; 2) Cherished relationships; 3) Prioritizing being presentable; 4) Creating a peaceful atmosphere. Patients with advanced cancer present different states at each stage of their disease progression, which requires dynamic understanding to provide more precise care. In addition, their demands for cherished relationships, a presentable style, and a peaceful atmosphere will also increase during this process. We need to pay attention to these moments that are meaningful to them for improving the quality of end-of-life care. Conclusion: This study explored the aesthetic experiences from the unique experiences of patients with advanced cancer in end-of-life care, thereby using aesthetic elements to create and cultivate a unique end-of-life care ideal, which will stimulate the creativity and respond to the special challenges of end-of-life care.